Model Rangkaian-T Pembangkit Listrik Tenaga Bayu untuk Analisis Aliran Daya Tiga-Fase - Rudy Gianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
Recently, penetration of wind power plant in electric power distribution system has increased significantly. The wind power plant penetration can affect the system’s steady state and dynamic conditions. Furthermore, as the electric power distribution system is usually unbalanced, it has to be analyzed in a three-phase manner. Therefore, in order for the system conditions to be properly evaluated, development of a three-phase model of the system components (including wind power plant) is necessary. This paper proposes a simple method for modeling and integrating fixed-speed wind power plant for steady state analysis (i.e., power flow analysis) of the three-phase distribution system. The proposed method is based on the T-circuit model which has previously been successfully applied to single-phase electric power systems. In this study, the single-phase T-circuit model is modified and extended so as to facilitate three-phase power flow analysis under unbalanced system conditions. Application of the proposed model in two three-phase distribution systems (i.e. 33-node and 25-node systems) is also investigated and presented in this paper. Results of the investigation show that the proposed method is valid and accurate.